The queen - Frears, Stephen; Mirren, Helen; Sheen, Michael; Cromwell, James ([place of publication not identified] : [Granada Screen Ltd.], 2006)
Diana the'People's Princess has died in a car accident in Paris. The Queen and her family decide that for the best, they should remain hidden behind the closed doors of Balmoral Castle. The heartbroken public do not understand and request that the Queen comforts her people. This also puts pressure on newly elected Tony Blair, who constantly tries to convince the monarchy to address the public.
Director of photography, Affonso Beato ; film editor, Lucia Zucchetti ; music by Alexandre Desplat.
Helen Mirren, Michael Sheen, James Cromwell, Helen McCrory, Alex Jennings, Roger Alam, Sylvia Syms.
Filmed on location in Scotland, London & Paris & Ealing Studios, England.
LPF: U
DVD format, NTSC, Region 3, Dolby Digital.
In English with English subtitle.
Keywords: Diana, -- Princess of Wales, -- 1961-1997 -- Death and burial -- Drama; Elizabeth, -- II, -- Queen of Great Britain, -- 1926- -- Drama; Blair, Tony, -- 1953- -- Drama; Mourning customs -- England -- Drama; Public relations and politics -- England -- Drama; Biographical films